The latent structure of variables of sports preparation and athletic prepardness based on physical conditioning contents in basketball - Jukic, I.; Milanovic, D.; Vuleta, D. (Kinesiology, 2005)
The research was conducted to determine the latent structure of the variables of characteristics of the sports preparation process and preparedness of basketball players of both sexes. The system for data collection was based on an expert assessment of the influence of the classes of conditioning preparation contents on certain characteristics of both the preparation process and the status of preparedness. The sample of en-tities (127) consisted of training contents aimed at the development of the motor, physiological and morphological characteristics of athletes, whereas the sample of variables (49) involved the characteristics of the preparation process. Eight factors were extracted by means of the factor analysis of attributes or variables under the G-K criterion. The factors exhausted 85.5 % of the total variance of the manifest space. The isolated latent dimensions (factors) were named as the factor of speed-related attributes of basketball, the factor of multilateral preparation of basketball players, the factor of an aerobic regimen of work and exertion of maximal force, the factor of basic preparation of basketball players, the factor of improving the soft tissues of basketball players, the uninterpretable factor, the factor of specific explosive strength of a vertical jumping ability type, and the factor of ball control.